Necrosis Contributes to the Development of Hypertension in Male, but Not Female, Spontaneously Hypertensive Rats. Issue 6 (December 2019) - Abdelbary, Mahmoud; Rafikova, Olga; Gillis, Ellen E.; Musall, Jacqueline B.; Baban, Babak; O'Connor, Paul M.; Brands, Michael W.; Sullivan, Jennifer C.
Abstract : Necrosis is a pathological form of cell death that induces an inflammatory response, and immune cell activation contributes to the development and maintenance of hypertension. Necrosis was measured in kidney, spleen, and aorta of 12- to 13-week-old male and female SHRs (spontaneously hypertensive rats); male SHRs had greater renal necrotic cell death than female SHRs. Because male SHRs have a higher blood pressure (BP) and a more proinflammatory T-cell profile than female SHRs, the current studies tested the hypothesis that greater necrotic cell death in male SHRs exacerbates increases in BP and contributes to the proinflammatory T-cell profile. Male and female SHRs were randomized to receive vehicle or Necrox-5—a cell permeable inhibitor of necrosis—from 6 to 12 weeks of age or from 11 to 13 weeks of age. In both studies, Necrox-5 decreased renal necrosis and abolished the sex difference. Treatment with Necrox-5 beginning at 6 weeks of age attenuated maturation-induced increases in BP in male SHR; BP in female SHR was not altered by Necrox-5 treatment. Necrox-5 decreased proinflammatory renal T cells in both sexes, although sex differences were maintained. Administration of Necrox-5 for 2 weeks in SHR with established hypertension resulted in a small but significant decrease in BP in males with no effect in females. These results suggest that greater necrotic cell death in male SHR exacerbates maturation-induced increases in BP with age contributing to sex differences in BP. Moreover, although necrosis is proinflammatory, it is unlikely to explain sex differences in the renal T-cell profile. Abstract : Supplemental Digital Content is available in the text.